Principal's Leadership Style and Its Relevance To Teacher Performance - Khofiyah Khofiyah (AS-SABIQUN, 2022)
Leadership is a person's behavior that can influence others, by providing motivation and support so that the person is willing to work hard in achieving the goals expected by the company or organization. This study uses a qualitative approach because it meets the characteristics of qualitative research, namely: (1) the condition of the object of natural research, (2) research as the main instrument, (3) descriptive, because the data collected is in the form of words not numbers, (4) more concerned with the process. The results of the research on the influence of the principal's leadership style on teacher performance at MI Nurul Falah Mlayang, Sirampog District, Brebes Regency, that the principal's leadership at MI Nurul Falah Mlayang, Sirampog District, Brebes Regency is included in the very strong category. The results of this study indicate that the leadership style applied by the agency is a democratic leadership style. The hypothesis test shows that leadership style has a positive and significant effect on teacher performance. This explains that the more democratic the leadership style applied, the higher the teacher's performance. This leadership style has the behavior of being happy to accept suggestions, opinions and criticism from subordinates. leadership style that needs to be maintained, especially in the aspect of involving teachers in decision making and the need to improve aspects where leaders must pay attention to the interests of teachers and the interests of institutions. The results of this study are supported by the theory put forward by Amirulla, Leadership is a person who has the authority to give assignments, has the ability to persuade or influence others with a good relationship pattern in order to achieve predetermined goals.